International Evaluation of China’s Beef Cattle Industry Development Level and Lagging Points - Xujun Li; Xiaoping Ma; Mingli Wang; Hao Zhang (Agriculture, 2022)
Quality, efficiency, safety and environmental protection are important directions for the development of animal husbandry in China. Taking China’s beef industry as an example, this study establishes a comprehensive index system from six industrial subsystems: resource endowment, production, consumption, quality, trade and environment. By comparison with the beef cattle industry in other countries, great effort is being made to position the development level of China’s beef industry and to determine its lagging points, according to the coupling coordination degree and relative development degree of each subsystem. Under the multidimensional development goals, the development level of China’s beef cattle industry shows a fluctuating upward-downward trend, and the resource endowment has a certain advantage, but the development of the production, consumption, quality and environmental subsystems is insufficient and lacks competitiveness. China’s beef cattle industry is less developed than in Brazil, the United States, Argentina, Australia and other countries in terms of production, consumption, quality, trade and environment. The industrial subsystems mainly present low-level coordination and operation, with lagging development of the production quantity and quality. According to the analysis of the industry’s weaknesses, China’s beef industry needs to promote the combination of planting and breeding, cost reduction, efficiency increase, and green breeding.